2021
DOI: 10.1002/brb3.2428
|View full text |Cite
|
Sign up to set email alerts
|

24‐hour ambulatory blood pressure alterations in patients with Parkinson's disease

Abstract: Objects Abnormal blood pressure (BP) regulation is a feature of autonomic dysfunction in Parkinson's disease (PD) patients. The present study was to analyze the BP alterations by 24‐h ambulatory BP monitoring in PD patients with different disease stages and subtypes. Methods 32 consecutive patients PD patients and 43 control patients in our hospital from 2017 to 2020 were included. The circadian BP rhythm was divided into three types according to the 24‐h ambulatory BP monitoring. Dipping was defined as an ave… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 26 publications
1
5
0
Order By: Relevance
“…93,94 was significantly higher than in the early stage of the PD group and the normal group, also the differences between these groups in both BPV and circadian BP rhythm measurements were statistically significant, although there was no significant difference between the groups of PD with predominantly tremor or non-tremor; This can allow BPV examination to detect the progression of a stage of PD or various abnormalities related to BP before other symptoms develop. 90,95 It is also in line with the findings of high SBP that is significantly associated with a decline of UPDRS III (Unified Parkinson's Disease Rating Scale III) motor scores and becomes a predictor of motor decline in PD because of high SBP as the risk factors for white matter hyperintensities development which increases the rate of motoric disability. [96][97][98] However, controlling blood pressure with therapy, especially in PD patients with hypertension, will be more difficult due to BPV caused by fluctuations in BP due to autonomic dysfunction and neuropsychiatric disorders and sleep disorders as complications of PD that disrupt BP stability.…”
Section: Brain Aging and Blood Pressure Variability In Dementia And P...supporting
confidence: 76%
See 2 more Smart Citations
“…93,94 was significantly higher than in the early stage of the PD group and the normal group, also the differences between these groups in both BPV and circadian BP rhythm measurements were statistically significant, although there was no significant difference between the groups of PD with predominantly tremor or non-tremor; This can allow BPV examination to detect the progression of a stage of PD or various abnormalities related to BP before other symptoms develop. 90,95 It is also in line with the findings of high SBP that is significantly associated with a decline of UPDRS III (Unified Parkinson's Disease Rating Scale III) motor scores and becomes a predictor of motor decline in PD because of high SBP as the risk factors for white matter hyperintensities development which increases the rate of motoric disability. [96][97][98] However, controlling blood pressure with therapy, especially in PD patients with hypertension, will be more difficult due to BPV caused by fluctuations in BP due to autonomic dysfunction and neuropsychiatric disorders and sleep disorders as complications of PD that disrupt BP stability.…”
Section: Brain Aging and Blood Pressure Variability In Dementia And P...supporting
confidence: 76%
“…PD as a CNS neurodegenerative disease also has autonomic dysfunction due to cardiac sympathetic nerve degeneration, which accounts for about 40% of non‐motor symptoms of PD, which can even occur earlier before the onset of motor symptoms, with signs such as changes in BPV from OH and postprandial hypotension to supine hypertension 90–92 . A meta‐analysis of case‐control studies by Ng and coworkers in Asian populations, showed that hypertension increases the risk of PD by 1.9 times, but there are genetic and environmental factors that may influence it because, in the Caucasian population, hypertension was found to be a protective factor of PD 16 .…”
Section: Brain Aging and Blood Pressure Variability In Dementia And P...mentioning
confidence: 99%
See 1 more Smart Citation
“…There are some common indicators of BPV, including standard deviation (SD), range, coefficient of variation (CV), and average real variability (ARV) (2). BPV has been reported to be risk a factor or associated with the progression of many diseases (3)(4)(5)(6)(7). Among patients with Parkinson's disease (PD), 24 h CV of DBP in the advanced PD group was significantly higher than that in the control group and the early PD group (3).…”
Section: Introductionmentioning
confidence: 99%
“…BPV has been reported to be risk a factor or associated with the progression of many diseases (3)(4)(5)(6)(7). Among patients with Parkinson's disease (PD), 24 h CV of DBP in the advanced PD group was significantly higher than that in the control group and the early PD group (3). Also, BPV was found to be related to the severity of obstructive sleep apnea (OSA) (4).…”
Section: Introductionmentioning
confidence: 99%